Experimental characterization of bond fatigue of carbon reinforced concrete. Issue 5 (26th November 2020) - Wagner, Juliane; Curbach, Manfred
Abstract: Due to the construction of more and more bridges out of textile respectively carbon reinforced concrete (CRC) or strengthening with it, the fatigue behavior of the material becomes more important and has to be investigated. However, next to the tensile load‐bearing behavior, the bond behavior is crucial as well. As for the carbon textiles used nowadays, concrete splitting gaines in importance as failure mode, a suitable test setup has to be found which allows representing realistic conditions. Therefore, in this paper, two different test setups—the double‐sided textile pull‐out (DPO) and the overlap test—are compared regarding their results in quasi‐static reference and residual strength tests as well as in fatigue tests with different bond lengths. In the end, it will be clear that one of the test setups clearly creates the more realistic results.